2004
DOI: 10.1242/jcs.01474
|View full text |Cite
|
Sign up to set email alerts
|

RXRα acts as a carrier for TR3 nuclear export in a 9-cis retinoic acid-dependent manner in gastric cancer cells

Abstract: GFP-TR3 cotransfected with RXRα was exported out of the nucleus in response to 9-cis retinoic acid. Moreover, specific reduction of RXRα levels caused by anti-sense RXRα abolished TR3 nuclear export. In contrast, specific knockdown of TR3 by antisense-TR3 or TR3-siRNA did not affect RXRα shuttling. These results indicate that RXRα is responsible for TR3 nucleocytoplasmic translocation, which is facilitated by the RXRα ligand 9-cis retinoic acid. In addition, mitochondrial TR3, but not RXRα, was critical for ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 74 publications
2
35
1
Order By: Relevance
“…We found that cytoplasmic localization of RXRa was correlated with better prognosis in melanoma patients. This could be explained by the virtue of RXR nongenotropic pathway, which involves cytoplasmic translocalization of RXRa from the nucleus resulting in the inhibition of cell growth and induction of apoptosis in various cancer cells (21,22). Therefore, it is possible that those melanoma patients who had more cytoplasmic RXRa did also have cell growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…We found that cytoplasmic localization of RXRa was correlated with better prognosis in melanoma patients. This could be explained by the virtue of RXR nongenotropic pathway, which involves cytoplasmic translocalization of RXRa from the nucleus resulting in the inhibition of cell growth and induction of apoptosis in various cancer cells (21,22). Therefore, it is possible that those melanoma patients who had more cytoplasmic RXRa did also have cell growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…conditions the RXR-mediated targeting of Nur77/NR4A1 and of the thyroid hormone receptor to mitochondria to promote apoptosis 53,54 . Thus, in addition to a simple, on-off regulatory mechanism of RXR expression, more subtle mechanisms affecting its cellular localization control RXR transcriptional activities and may generate novel functions for this multi-faceted nuclear receptor.…”
Section: 6mentioning
confidence: 99%
“…Inhibition of Nur77 expression by antisense RNA prevents the apoptotic effect of AHPN/CD437. Rapid induction of Nur77 also occurs in cancer cells after stimulation of apoptosis by a variety of apoptosis-inducing agents, including calcium ionophores, etoposide (VP-16) (Li et al, 2000;Liu, 2002), and phorbol ester (Li et al, 2000;Liu, 2002;Cao et al, 2004a;Lin et al, 2004b), synthetic chenodeoxycholic acid derivatives (Jeong et al, 2003), Di-n-butyltin dichloride (Gennari et al, 2002), histone deacetylase inhibitors (Chinnaiyan et al, 2006), cadmium (Shin et al, 2004), 1,1-bis(3 0 -indolyl)-1-(p-substituted phenyl)-methanes (Chintharlapalli et al, 2005), and induced Nur77 contributes to their apoptotic effects.…”
Section: Nur77 As a Death Factormentioning
confidence: 99%